Early Glycemic Response Predicts Achievement of Subsequent Treatment Targets in the Treatment of Type 2 Diabetes: A Post hoc Analysis. Issue 3 (September 2015) - Fu, Haoda; Cao, Dachuang; Boye, Kristina; Curtis, Bradley; Schuster, Dara; Kendall, David; Ascher-Svanum, Haya
Abstract Introduction American Diabetes Association consensus guidelines emphasize individualized treatment in the management of type 2 diabetes mellitus (T2DM). Early glycemic response is a clinical marker that may predict longer term efficacy for individual patients and provide a clinical tool to enhance personalized treatment. This analysis evaluated whether glycemic response measured at week 12 ("early") could serve as a reliable predictor of glycemic control at weeks 24 and 52 of therapy in patients with T2DM. Methods We used data from 3 randomized, controlled clinical trials that evaluated patients with T2DM treated with 3 commonly prescribed glucose-lowering medications: metformin (n = 597), sulfonylurea (n = 626), and insulin glargine (n = 1046). The gradient boosting method was used to identify predictors of subsequent response; predictive accuracy was represented by sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV). Treatment success at weeks 24 and 52 was assessed for each patient and defined as achieving a glycated hemoglobin (HbA1c ) level of <7.0% or a reduction from baseline of ≥1.0%. Results The predictive parameters (sensitivity, specificity, PPV, and NPV) for improvements in HbA1c at week 24 for metformin were 0.83, 0.81, 0.44, and 0.96; for sulfonylurea, 0.79, 0.94, 0.71, and 0.96; and for insulin glargine, 0.67, 0.89, 0.65, and 0.90. The predictive parameters for improvements in HbA1c at week 52 for metformin were 0.73, 0.84, 0.56, and 0.92 and for sulfonylurea, 0.45, 0.94, 0.74, and 0.82. Conclusion High predictive values identified in this analysis support "early" response as an appropriate tool for predicting treatment success at weeks 24 and 52. The high NPV (lack of early glycemic response) appears to be an effective indicator of the likely need for change in (or intensification of) therapy. These data support the current guideline recommendations that clinicians evaluate therapeutic responses to pharmacologic interventions with metformin, sulfonylureas, or insulin glargine as early as week 12.